Interfacial properties of protein particles at fluid/fluid interfaces and relationship with the stability of foams and emulsions - Fameau, Anne-Laure; Guzmán, Eduardo; Ritacco, Hernán Alejandro; Saint-Jalmes, Arnaud (Frontiers in Soft Matter, 2023)
It is now well-known that the assembly of particles at fluid/fluid interfaces, and the resulting dynamical properties of such particle-laden interfaces can provide high stabilization of dispersed systems such as emulsions and foams. Here, we focus on the emerging case of “protein particles,” a novel family of bio particles. We provide an updated perspective about their definition, production, bulk and interface properties, highlighting the most recent results of the obtained bioparticle-laden interfaces, and how such protein particles can stabilize liquid dispersions. The ability of protein particles for undergoing a fast adsorption to fluid/fluid interfaces and for forming viscoelastic layers play a key role on the prevention of drainage, coalescence, or coarsening/ripening, which results in the formation of very stable particle-stabilized foams and emulsions. Therefore, protein particles are an excellent bio-based alternative to synthetic surfactants and other conventional stabilizers for ensuring the stabilization of a broad range of dispersed systems, opening new avenues for the design of new products with interest for cosmetic, food and biomedical industries.